The afferent pupillary defect in acute optic neuritis. - Ellis, C J (1979)
Twenty-two patients with acute optic neuritis were studied by the techniques of infrared pupillometry and visual evoked responses (VER) to pattern reversal. A relative afferent pupillary defect was found in all cases and the magnitude of this defect was found to be related to the amplitude, but not to the latency, of the VER. During follow-up the afferent defect was found to remain persistently abnormal while other methods of clinical evaluation could not demonstrate abnormality reliably. The amplitude of the VER also remained low.